Performance of Garut breed rams fed diets containing various cation-anion difference with or without fish oil supplementation - Rahmat Hidayat; T. Toharmat; A. Boediono; I.G. Permana (Jurnal Ilmu Ternak dan Veteriner, 2011)
This study was carried out to evaluate the effect of dietary cation-anion difference (DCAD) and fish oil supplementations on dry matter intake (DMI), dry matter digestibility (DMD) and organic matter digestibility (OMD), weight gain, as well as the acidity of urine in Garut breed rams. The experiment was done based on randomized group design with 6 treatments  and 3 groups. The dietary treatments were as follows: R0= basal ration (DCAD +14) without fish oil, R1 = basal ration (DCAD +14) with 3% fish oil, R2 = base ration (DCAD +40) without fish oil, R3 = base ration (DCAD +40) with 3% fish oil, R4 = acid ration (DCAD -40) without fish oil, and R5 = acid ration (DCAD -40) with 3% fish oil. All rations contained 150 ppm of zinc and were offered to 18 of Garut breed rams. The results indicated that DCAD +40 and -40 decreased DMI significantly.  The ration with DCAD +40 had the lowest DMI. Fish oil supplementation decreased DMI. No differences were observed for DMD and OMD.  DCAD +40 and -40 decreased body weight of rams. However, the body weight of rams was very low. Variation of urine pH followed the DCAD pattern. It was concluded that DCAD +40 and -40, as well as fish oil supplementations decreased DMI, body weight and urine pH followed the DCAD pattern. Keys Words: Cation, Anion, Body Weight, Digestibility, Garut Breed Rams